2 Records of the Colony of Rhode Island and Providence Plantations, in New England 561 (1857) - (:unkn) unknown (My University, 1677)
Required seizure of guns and ammunition from “any Indian.”
Keywords: ENSLAVED PERSONS & OTHER MINORITIES